The AI Co-Author: Investigating the Impact of Generative AI on Creative Short Story Writing Skills on the Students of English Education Study Program - Christmas Prasetia Ate; Dortean Amelia Jois Jaha (Universitas Citra Bangsa, 2026)
This qualitative case study investigates the impact of Generative AI (GenAI) as a